Pengaruh Modal Usaha, Lokasi Usaha, Dan Teknologi Informasi Terhadap Pendapatan Kampung Wisata Kelengkeng Desa Simoketawang Kabupaten Sidoarjo - Mitha Anggraini; Maulidah Narastri (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The aim of this research is to examine the influence of business capital, business location and technological information on the income of the Kelengkeng Tourism Village, Simoketawang Village, Sidoarjo Regency. The method used in this research uses quantitative methods. The research used purposive sampling techniques and data collection through questionnaires delivered to respondents and the results of multiple linear regression data analysis showed that information on business capital, business location and technology had a positive effect on income. The greater the capital generated, the greater the income earned. Choosing a strategic location can influence income. And take advantage of developing technological sophistication to help promote its business.